Chronically stimulated human MAIT cells are unexpectedly potent IL‐13 producers. Issue 8 (19th July 2019) - Kelly, Jason; Minoda, Yosuke; Meredith, Tobias; Cameron, Garth; Philipp, Marie‐Sophie; Pellicci, Daniel G; Corbett, Alexandra J; Kurts, Christian; Gray, Daniel HD; Godfrey, Dale I; Kannourakis, George; Berzins, Stuart P
Abstract: Mucosal‐associated invariant T (MAIT) cells are unconventional T cells that recognize antigens derived from riboflavin biosynthesis. In addition to anti‐microbial functions, human MAIT cells are associated with cancers, autoimmunity, allergies and inflammatory disorders, although their role is poorly understood. Activated MAIT cells are well known for their rapid release of Th1 and Th17 cytokines, but we have discovered that chronic stimulation can also lead to potent interleukin (IL)‐13 expression. We used RNA‐seq and qRT‐PCR to demonstrate high expression of the IL‐13 gene in chronically stimulated MAIT cells, and directly identify IL‐13 using intracellular flow cytometry and multiplex bead analysis of MAIT cell cultures. This unexpected finding has important implications for IL‐13‐dependent diseases, such as colorectal cancer (CRC), that occur in mucosal areas where MAIT cells are abundant. We identify MAIT cells near CRC tumors and show that these areas and precancerous polyps express high levels of the IL‐13 receptor, which promotes tumor progression and metastasis. Our data suggest that MAIT cells have a more complicated role in CRC than currently realized and that they represent a promising new target for immunotherapies where IL‐13 can be a critical factor. Abstract : Mucosal‐associated invariant T (MAIT) cells are regarded as proinflammatory lymphocytes with a Th1/Th17 cytokine response. This study shows human MAIT cells can also be prominent IL‐13‐producing cells. The findings shed new light on the potential role of MAIT cells in tumor immunity and their potential as new targets for immunotherapies in colorectal cancer and other IL‐13‐dependent diseases.